BASIS EPISTEMOLOGIS PARADIGMA RASIONAL DALAM ILMU HUKUM: SEBUAH DESKRIPSI TENTANG ASUMSI-ASUMSI DASAR TEORI HUKUM MURNI-HANS KELSEN - Kelik Wardiono; Khudzaifah Dimyati (Jurnal Dinamika Hukum, 2014)
Based on the philosophical approach, it is known basic assumptions of rational paradigm as seen in Hans Kelsen's pure theory of law that consists of: human assumptions based on the quasi-transcendental along with its characters and aurea aetas; ontological assumptions based on empirical reality and equating sein reality with sollen, and normativity created as logico transcendental conditions; epistemological assumption that underlying the science of law as cognitive science, creating the rule of law as a whole object, and reconstructing legal norm as the relation between non-causal and non-metaphysical facts; axiological assumption that reconstructs norm as the object of legal science and equating the basic norms with natural laws.Key words: basic assumptions, rational paradigm, the theory pure of law, jurisprudance.